Study on the business strategy and model for river-water hydrothermal energy - YOO, Sung Jae (KDI School, 2024)
This study delves into the business models and strategies pertaining to the utilization of hydrothermal energy extracted from deep dam water and river water in South Korea. The research undertakes an assessment of potential capacities, devise model strategies and designs, and evaluates their economic viability. Key findings indicate that deep dam water holds suitability for national-scale projects targeting energyintensive clusters, necessitating accurate post-project conception calculations of actual potential. The study proposes strategic indicators and hierarchical weighting analysis for comprehensive evaluation. In the context of river water, the research identifies its viability for heating and cooling large urban buildings, albeit requiring meticulous return on investment evaluation due to high initial costs. Continuous updates on the Coefficient of Performance (COP) of heat pumps based on project-specific factors are deemed essential. The study underscores the critical importance of precise Return On Investment calculations and potential improvement measures in implementation design, advocating for diversified evaluation methods that encompass policy considerations, operational data collection, and international case studies.
Thesis(Master) -- KDI School: Master of Public Management, 2024
Keywords: Renewable energy sources--Korea (South); Water-supply--Korea (South)